2022
DOI: 10.1016/j.tranon.2021.101292
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 18F-PSMA-1007 PET/CT in prostate cancer patients with biochemical recurrence after radical prostatectomy

Abstract: Highlights 18 F-PSMA-1007 PET/CT demonstrated a high detection rate for PCa patients with a raised PSA level after radical prostatectomy. PSMA-positive lesions were detected in 56 (56/71, 79%) patients. The detection efficacy for patients with PSA level >2.0 ng/mL, 1.1 to ≤2.0 ng/mL, 0.51 ng/mL to ≤1.0 ng/mL and ≤0.5 ng/mL was 100% (28/28), 100% (8/8), 80% (4/5) and 50% (14/28), respectively. Patients with ADT were more likely to have a high detection rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Xing Zhoe et al, while evaluating BCR in patients following RP, found a high detection rate for patients after radical prostatectomy. In their study, 79% of patients showed at least one pathological finding on 18 F-PSMA-1007 PET/CT [8]. Treglia G et al performed a systematic review and meta-analysis for the detection rate of 18 F-labeled PSMA PET/CT in BCR of PCa and found a pooled diagnostic rate of 81% for 18 F-labeled PSMA PET/CT [9].…”
Section: Discussionmentioning
confidence: 97%
“…Xing Zhoe et al, while evaluating BCR in patients following RP, found a high detection rate for patients after radical prostatectomy. In their study, 79% of patients showed at least one pathological finding on 18 F-PSMA-1007 PET/CT [8]. Treglia G et al performed a systematic review and meta-analysis for the detection rate of 18 F-labeled PSMA PET/CT in BCR of PCa and found a pooled diagnostic rate of 81% for 18 F-labeled PSMA PET/CT [9].…”
Section: Discussionmentioning
confidence: 97%
“…Most metastases shown by 18 F-PSMA-1007 and 18 F-FDG PET/CT have typical imaging ndings. Existing studies have shown a high correlation between PSMA-positive lesions and pathologically con rmed metastases [37]. We recruited three senior nuclear medicine physicians to read independently to avoid misjudgment.…”
Section: Discussionmentioning
confidence: 99%
“…The two most commonly used radiolabels for PSMA are gallium-68 [ 68 Ga] or fluoride-18 [ 18 F] [108,109]. A recent systematic review by Evangelista et al found limited headto-head evidence between the two radiolabels but noted a number of factors to take into account.…”
Section: Detection Of Recurrent Diseasementioning
confidence: 99%